Parents' Attitudes toward COVID-19 Vaccination: A Study from Two Centers in Istanbul - Saka, Selve Çınaroğlu; Kafi, Hale Molla; Çakın, Zeynep Ebru; Fırat, Cem Koray; Toprak, Ali; Türel, Özden (Journal of Pediatric Infectious Diseases, 2023)
Objective Vaccination is an important measure for the prevention of coronavirus disease 2019 (COVID-19). In the present study, we aimed to evaluate parents' attitudes toward vaccinating themselves and their children. We also searched whether information about the multisystem inflammatory syndrome in children (MIS-C), a severe complication of COVID-19, could change parents' decisions on vaccinating their children.Methods A questionnaire form consisting of sociodemographic features, COVID-19 vaccination practices, and knowledge about MIS-C was applied to parents of children attending Bezmialem Vakıf University Hospital from March through June 2022. Factors affecting vaccine hesitancy were evaluated.Results Among 383 parents, COVID-19 history was present in 248 (64.8%), and 165 (43.1%) were hesitant to vaccinate themselves. The number of cases where both parents had received at least one dose of COVID-19 vaccine was 256/354 (72.3%). The most common reasons for vaccine hesitancy were vaccines being new in 53/165 (32.1%) and fears of side effects in 95/165 (57.6%). Parents' hesitation toward vaccination of their children with the COVID-19 vaccine was highest for the 0 to 6 age group (78.9%) (73.6% in the 6–12 age group, and 47.3% in the 12–18 age group). In total, 365/383 (95.3%) parents did not have an opinion about MIS-C. After information was given, 62.5% of the 302 participants who opposed vaccinating children under 6 years changed their decision to have their children vaccinated.Conclusion Although routine childhood vaccinations were performed in 99% of children, more than half of parents were hesitant to vaccinate their children with the COVID-19 vaccine. The majority did not have an opinion about MIS-C. Briefings by pediatricians about complications of COVID-19 will help avoid vaccine hesitancy.
Keywords: COVID-19; COVID-19 vaccine hesitancy; MIS-C; parent